Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 23, 1930 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1930)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, January 23, 1930. Hawley spent the Christmas holidays in 1872 in Connecticut but was back in Washington soon after the first of the year. A group of capitalists organized a company and proposed to lease an enormous tract in the Island of San Domingo for speculative purposes. Hawley foresaw that the country might be embroiled as result of such a venture, and he was opposed to it. Reconstruction was still making much trouble. In Louisiana there were four claimants for the governorship. Warmouth, who aspired to be senator claimed the office and so did Pinchback, colored lieutenant governor elect. Other claimants were John McEnery, democratic candidate in the election of 1872 and Kellogg. Two legislatures met and the state was in turmoil. Troops were called out and the federal government had to intervene.
1 electronic record. Scanned newspaper article. 2 image scans. 1.41 MB (1,479,669 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 39.8 MB (41,793,316 bytes).
Keywords: Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); United States--History--Civil War, 1861-1865; Personal correspondence; Letters; Newspapers